Fifth annual report - Mew, E. B. ; Miller, Mary F. ; Norman, E. M. ; Roberts, D. ; Galbraith, H. ; Worden, M. ; Daukes, A. ; Waterworth, E. M. ; Mottram, D. B.; Capener, Norman (1932)
1932 1932 1930s 86 pages : illustrations DEVONIAN ASSOCIATION FOR CRIPPLES' AID. A2. GENERAL FUND. INCOME ACCOUNT. RECEIPTS AND PAYMENTS ACCOUNT FOR THE YEAR ENDED 31ST DECEMBER, 1932. RECEIPTS. £ s. d. To Annual Subscriptions 115 1 6 „ Donations, Collections, etc. 133 14 9 „ Entertainments 227 8 1 „ Other Receipts — Contributions to Industry Instructress' Salary 17 10 0 Advertisements 11 11 0 Sundries 5 17 6 34 18 6 „ Rents 25 0 0 „ Transfer from Hospital Account 120 15 0 „ Special Donation from the Bernhard Baron Trust Fund 100 0 0 £756 17 10 PAYMENTS. £ s. d. £ s. d. By Bank Overdraft, 1st January, 1932 6 13 0 Less Cash in hand 1 15 0 4 18 0 „ Printing and Stationery 65 8 2 „ Salaries and Travelling Expenses — T.W.D. 274 3 8 „ Contribution to Travelling Expenses of Instructress 20 0 0 „ Subscription, Central Council 5 5 0 „ Collecting Boxes 2 10 0 „ Entertainment Expenses 5 0 0 „ Transport 1 10 0 „ Sundries 6 5 11 „ Bank Charges 4 1 0 „ Board and Special Grants to Patients 317 0 11 Less received from Patients, Clinic Committees and Local Authorities 199 4 6 117 16 5 „ Industry, Expenses of Car 10 19 6 „ Clinic Account 20 8 3 „ Medical Officer's Honorarium 120 15 0 „ Balance at Bank, 31st Dec., 1932 92 19 11 „ Petty Cash in hand 4 17 0 97 16 11 £756 17 10 We have examined the above Account with the Books and Vouchers, and certify the same to be correct in accordance therewith. WARE, WARD & Co., Chartered Accountants, Auditors. Exeter, 27th February, 1933. 36 292/841.51/2/2